HUBUNGAN BBLR, PEMBERIAN ASI EKSKLUSIF, DAN RIWAYAT DIARE DENGAN KEJADIAN STUNTING PADA BADUTA (0-23 BULAN) DI SULAWESI BARAT : ANALISIS DATA SEKUNDER RISKESDAS 2018 - Raden Ayu Rizka Rochmatika (2023)
Stunting is a failure of growth and development experienced by children due to inadequate nutritional intake for a long time. The purpose of this study was to analyze the relationship between low birth weight, exclusive breastfeeding, and a history of diarrhea with the incidence of stunting among children under 2 years old in West Sulawesi. This study used a quantitative approach with a cross-sectional study design and used secondary data from Riskesdas 2018. Bivariate analysis was performed using the chi-square test and followed by multivariate analysis using binary logistic regression. Bivariate test results showed that there was no significant relationship between low birth weight (p value = 0.651 > 0.05), exclusive breastfeeding (p value = 0.566 > 0.05), and diarrhea (p value = 0.763 > 0.05) with the incidence of stunting. And the results of the multivariate test showed that there was no effect between LBW (p value = 0.651 > 0.25), exclusive breastfeeding (p value = 0.566 > 0.25), and diarrhea (p value = 0.763 > 0.02) with the incidence of stunting. There are various ways to prevent stunting. One of them is by knowing and understanding the factors that can trigger stunting, for example, age, gender, mother's education, mother's occupation, place of residence, low birth weight, exclusive breastfeeding, and history of diarrhea. Parents can take this preventive step so that their child does not experience stunting. Keywords : Children under 2 years old, exclusive breastfeeding, LBW, history of diarrhea, stunting